PERAN PEMERINTAH DESA DALAM PELAKSANAAN PROGRAM BANTUAN LANGSUNG TUNAI SEBAGAI UPAYA PENANGANAN COVID-19 DI DESA KASANG LIMAU SUNDAI KECAMATAN KUANTAN HILIR SEBERANG KABUPATEN KUANTAN SINGINGI TAHUN 2020 - ', Rafli; Tinov, M. Y. Tiyas (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The aim of this research is to determine the role of the village government in implementing the Direct Cash Assistance Program as an effort to handle COVID-19, Kasang Limau Sundai Village, Kuantan Hilir Seberang District, Kuantan Singingi Regency and aspects that influence the success of the village government's role in implementing the Direct Cash Assistance Program as an effort to handle COVID-19. 19 in Kasang Limau Sundai Village, Kuantan Hilir Seberang District, Kuantan Singingi Regency. The research method used is qualitative description, namely describing the current state of the object qualitatively using data obtained from research. The data sources used are primary data sources and secondary data with a total of 8 informants. Data collection techniques use observation, interviews and documentation methods. The analysis techniques used are data reduction, data presentation and drawing conclusions. The research results show that: First, the role of the village government as a regulator in Kasang Limau Sundai Village is to issue Kasang Limau Sundai Village Head Decree Number 14 of 2020 and issue a Certificate of Formation of COVID-19 Village Volunteers. Second, the role of the village government as a facilitator in Kasang Limau Sundai Village is to provide assistance through training, education and skills improvement, as well as working in the field of financing and capital by providing financial assistance to empowered communities. Third, the role of the village government as a dynamist in Kasang Limau Sundai Village is to invite community leaders to take part in the Special Village Conference (Musbangun) to determine potential recipients of Direct Village Fund Cash Assistance. The three aspects that influence the success of the village government's role in implementing the Direct Cash Assistance Program as an effort to handle COVID-19 in Kasang Limau Sundai Village include policy socialization, determining program recipient targets and coordination in implementation. Keywords: Role of Village Government, COVID-19, Direct Cash Assistance Program